UTILIZATION OF LINGO APPLICATION IN OPTIMIZING SNACKS USING LINEAR PROGRAM: PEMANFAATAN APLIKASI LINGO DALAM OPTIMALISASI MAKANAN RINGAN MENGGUNAKAN PROGRAM LINEAR - Djeni, Darwin; Waluyo, Eko; Hasanah, Husnul (Department of Mathematics Education , University of Jember, 2024)
Micro-enterprises in the snack food sector often face various challenges, including limited raw materials, high production costs, and fluctuating market demand. This study aims to optimize the production of snack foods such as sausage corndogs, cheese corndogs, and chocolate banana rolls (piscok) through the application of linear programming using the LINGO software. The research employs a quantitative descriptive approach with field observations conducted on the researcher’s own business located in Bulang Village, Probolinggo Regency. A mathematical model was developed by taking into account real-world constraints such as production capacity and raw material availability, with the goal of maximizing profit. The analysis using LINGO indicates that the optimal production combination consists of 20 sausage corndogs, 5 cheese corndogs, and 20 piscok per day, resulting in a maximum daily profit of IDR 75,000. These findings suggest that the use of LINGO software can significantly assist micro-entrepreneurs in managing resources more efficiently and enhancing the profitability of snack food businesses.